Usulan Kebijakan Persediaan Bahan Baku dengan Metode Lot Sizing pada Perusahaan Manufaktur Gelas Plastik - Mirna Lusiani; Eko Verdianto (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
This research was made with the aim to make production planning and inventory control in manufacturing company of plastic glass, especially for main raw material from 14 oz plastic cup product, that is Resin-HE 2.0 and whitening using lot sizing method. Due to the fluctuating demand and the accumulation of raw materials in the warehouse, the company needs for production planning and inventory control. The lot-sizing method used in this research is Period Order Quantity (POQ), Lot For Lot (LFL) and Fixed Period Requirement (FPR) which each method have a different concept. The result by using FPR Method 3 weeks and LFL in inventory control will give the lowest inventory cost to the company that is equal to Rp. 159.400,00 for Resin-HE 2.0 and Rp. 39.600,00 for whitening.